Lessons for the COVID era and beyond: The impact of inactive lifestyle and mental health events on burnout syndrome in university professors working from home during the pandemic - Angelica Castilho Alonso; Alan Oliveira Máximo de Carvalho; Juliana Sanches Lira; Vitória Camargo Paixão; Rafael Diego Modenes; Rita de Cássia Ernandes; Vanderlei Carneiro da Silva; Gerson Scherrer Júnior; Kleyton Góes Passos; Matheus Henrique dos Santos Lino; Sofia Silva; Sónia Brito-Costa; et al. (Heliyon)
The rapid shift to remote work due to the COVID-19 pandemic has profoundly impacted work environments, intensifying challenges related to mental health and burnout among university professors. This study aimed to evaluate the presence of Burnout Syndrome (BS) in university professors following the adoption of remote home work (RHw) mandated by COVID-19 health measures and to identify key predictors, including both risk and protective factors. Virtual questionnaires were administered to 345 professors of both genders, collecting data on bio-sociodemographic, clinical health and lifestyle screen. The Maslach Burnout Inventory was used to assess BS. Results showed high levels of emotional exhaustion, low levels of depersonalization, and moderate levels of reduced personal accomplishment among professors. Protective factors against emotional exhaustion included older age, lack of irritation with RHw, and regular physical activity, while risk factors included excessive workload, dissatisfaction, irritability, fatigue, changes in body mass, and physical inactivity. Older professors showed lower levels of depersonalization, while body mass changes and frequent alcohol consumption increased it. For reduced personal accomplishment, protective factors included older age, greater work experience, and employment in private institutions, whereas dissatisfaction was a risk factor. Findings indicate that RHw results in chronic stress for professors, primarily through emotional exhaustion. Key contributing factors include excessive workload, dissatisfaction, irritability, fatigue, and pandemic-related lifestyle changes, while protective factors include older age, positive attitudes toward RHw, and regular physical exercise.